Analisis Pendayagunaan ZISWAF sebagai Solusi Pembiayaan Pendidikan (Studi Kasus Keluarga Kurang Mampu Kota Bekasi) - Muhammad Hasyim Asyhari; Deni Irawan (Jurnal Ilmiah Ekonomi Islam, 2023)
This study aims to determine the utilization of ZISWAF as a solution to financing education at BAZNAS Bekasi City with the current program, called â€œBekasi Cerdasâ€. Through the utilization of ZISWAF for solutions to improve the education of the underprivileged, it is hoped that it can assist in providing access to education for people in Indonesia, especially in Bekasi City, especially for those who are economically constrained, so that these children get quality education. The research was conducted using a qualitative approach with descriptive analysis methods and data sources from literature studies such as books, journals, articles, and information related to this research. The results obtained from this study are that the Bekasi City BAZNAS has channeled ZISWAF funds for the Education sector through the "Smart Bekasi" program of Rp. 2,628,200,000 for 5,395 mustahik to support their access to education to improve it and make them more enthusiastic in pursuing their goals so that these ZISWAF funds are used productively in developing humans.